Catecholaminergic effects on inhibitory control depend on the interplay of prior task experience and working memory demands. (June 2019) - Bensmann, Wiebke; Zink, Nicolas; Roessner, Veit; Stock, Ann-Kathrin; Beste, Christian
Background: Catecholamines affect response inhibition, but the effects of methylphenidate on inhibitory control in healthy subjects are heterogenous. Theoretical considerations suggest that working memory demands and learning/familiarization processes are important factors to consider regarding catecholaminergic effects on response inhibition. Aims: The purpose of this study was to examine the role of working memory demands and familiarization for methylphenidate effects on response inhibition. Methods: Twenty-eight healthy adults received a single dose of methylphenidate (0.5 mg/kg) or placebo in a randomised, double-blind, crossover study design. The subjects were tested using a working memory-modulated response inhibition paradigm that combined a Go/Nogo task with a mental rotation task. Results: Methylphenidate effects were largest in the most challenging mental rotation condition. The direction of effects depended on the extent of the participants' task experience. When performing the task for the first time, methylphenidate impaired response inhibition performance in the most challenging mental rotation condition, as reflected by an increased false alarm rate. In sharp contrast to this, methylphenidate seemed to improve response execution performance in the most challenging condition when performing the task for the second time as reflected by reaction times on Go trials. Conclusion: Effects of catecholamines on inhibitory control processes depend on the interplay of two factors: (a) working memory demands, and (b) learning or familiarization with a task. It seems that the net effect of increases in gain control and decreases in working memory processes determines the methylphenidate effect on response inhibition. Hence, crossover study designs likely underestimate methylphenidate effects on cognitive functions.